23. Bienal Internacional Sao Paulo. - Afgany, Jmal; Aguilar, Nelson; Alexis, Grald; Ardila, Maria Elvira; Bill, Simon; Bischoff, Willlem; Braff, Phyllis; Camacho, Doreen M. Colón; Cancelier, Simone; Cazali, Rossina; Chang, Tsong-zung; Chapot, André; et al. (São Paulo : Fundaçao Bienal de São Paulo, 1996)
Abath, Ciro ; Ayesta, Ezequiel Padilla ; Barakat, Tayseer ; Blazeska, Violeta ; Boshoff, Willem ; Boxer, David Wayne ; Boyadjiev, Bojidar ; Branch, Winston ; Bruguera, Tania ; Burnside-Beadle-Burnside ; Caldas, Waltercio ; Canas, Carlos ; Capellan, Tony ; Carrilho ; Cavenago, Umberto ; Chichkan, Illya ; Claassen, Tom ; Cornet, Heleen ; Delgado, Leandro Silva ; Demur, Boris ; Duval-Carrié, Edouard ; Fink, Christoph ; García-Sevilla, Ferran ; Gardner, Joscelyn ; Grabuloski, Bogdan ; Hausswolff, Annika von ; Heske, Marianne ; Ho Siu-kee ; Hume, Gary ; Hydes, Bendel ; Jorarsaa ; Keskküla, Ando ; Kim, Tschoo-Su ; Klasmer, Gabriel ; Kobayashi, Masato ; Koller, Julius ; Latamie, Marc ; Lawaetz, Roy ; Lemmerz, Christian ; Leogane, Lucien ; LeWitt, Sol ; Lombardi, Inés ; Madi, Hussein ; Mezza, Gonzalo ; Moffatt, Tracey ; Mostafa, Ramzi ; Namizato, Eduardo Tokeshi ; Navalainen, Pekka ; Navridis, Nikos ; Ngui, Matthew ; O'Kelly, Alanna ; Otero, Néstor ; Palma, Luis Gonzalez ; Paraskos, Stass ; Patatitcs, Alexandru ; Penalva, João ; Pinto, Xavier Blum ; Restrepo, José Alejandro ; Robinot, Roseman ; Rodriguez, Juan Luis ; Rondinone, Ugo ; Sacco, Graciela ; Séchas, Alan ; Simoncic, Petra Varl ; Sirait, Marintan ; Soto, Jesus Rafael ; Spatuzza, Carlo ; Suter, Gerardo ; Tho, Tran ; Urbinati ; Veress, Zsolt ; Vidová-Zackova, Janka ; Wolff, Carl Emanuel ; Yingqi, Jiao ; Zelenka
biografie
23. Bienal Internacional Sao Paulo, 5 de outubro a 8 dezembro de 1996, Pavilhão Ciccillo Matarazzo, Parque do Ibirapuera, São Paulo, 1996
Portugees & Engels
boek